The need for a mortality database in Pakistan: now or never - Qureshi, Sidra Waqar; Erum Anwar (Journal of the Pakistan Medical Association, 2024)
Respected editor, With a staggering figure of 241.5 million inhabitants, Pakistan is considered the fifth most populous country in the world, with a growth rate of 2.55% per annum. (1) The crude mortality rate as per Pakistan Demographic Survey 2020, was 6.7 per 1000 persons (2), however, data regarding causes of death is doubtful, since a good number of diseases are never truly diagnosed, especially those occurring at homes or in rural areas, while many remain unregistered. Worldwide, mortality statistics serve as an essential indicator of the health and well-being of a population. Maintenance of up-to-date records is considered an important component of health-care policy making, public health research, and future resource allocation, as they help in assessing community health status, and subsequently aid in modifying factors that can ensure better lives. The CDC WONDER database, for example, contains mortality statistics of the U.S. population, collected from the millions of death certificates, from over the past two decades, and is available online. (3) However, in Pakistan, no such reliable mortality database exists at the national level, which could serve a similar purpose. Although the Civil Registration and Vital Statistics (CRVS) system for Pakistan has been in existence for long, its online record lacks statistics regarding causes of death. (4) It is a dilemma, that a significant number of deaths, 40% according to WHO (5), remain unregistered, while those that are registered do not contain an accurate diagnosis of diseases that ultimately lead to loss of lives. It is only reasonable that an accurate and timely updated mortality database be maintained on a nationwide level, based off of death certificates issued by healthcare facilities. A standardized death certificate introduced throughout the country, can not only help recognize the leading causes of death, but could also aid in overcoming inadequacies when it comes to maintaining accurate health records. Such measures can prospectively allow researchers to document long-term survival statistics for clinical research, to identify potential risk factors for certain conditions and recognize high-risk populations so that early preventative care and interventions can be undertaken.